TINJAUAN TERHADAP PERJANJIAN STANDAR DALAM PERJANJIAN KREDIT PERBANKAN - Eman Sulaiman (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2018)
Customers as economic actors are very weak in terms of legal protection, for example their position in standard agreements (standard contract). Debt agreements through bank credit, including short-term, medium and long-term credit. The standard agreement in the banking credit agreement between the bank as a creditor with the customer as a debtor is contrary to the principle of freedom of contract, even decency. This is due to the legal position of the debtor is not balanced with the creditor.